Pelatihan Rancang Bangun Tiang Lampu Penerangan Jalan Desa Ciramahilir Kecamatan Maniis Kabupaten Purwakarta - Muhammad Chusnan Aprianto; Mochamad Abdul Muftinur; Audi Murfi Siregar; Jeje Herdiana; Dadi Permadi (Jurnal Kemitraan Masyarakat, 2025)
This community service activity aims to enhance the technical capacity and participation of residents in designing and constructing streetlight poles in Ciramahilir Village, Purwakarta Regency. The village's main issue is the lack of street lighting, which affects safety and community activities at night. The implementation method used a participatory approach through the formation of a working group, technical training, and hands-on installation using appropriate technology. The results showed improved technical skills among residents, successful installation of lights in dark-prone areas, and the establishment of a community-based maintenance structure. This success indicates that locally driven training combined with active community involvement can serve as an effective strategy to address rural infrastructure problems independently and sustainably